DIFFERENCE BETWEEN ELECTRONIC SIGNATURE AND DIGITAL SIGNATURE - Nimwat, Danita; Rakprasertsuk, Chamorn (Rangsit Journal of Law and Society, 2023)
Electronic signature and digital signature are two methods used to sign electronic documents as well as to verify the authenticity and integrity of these documents. therefore, it is widely popular in industries such as finance, medical, real estate and government However, there are still differences in legal implications. Signature security level and types of electronic documents using electronic signatures and digital signatures. An electronic signature is a symbol or mark. Created from a simple electronic process to express an individual’s consent to the content of electronic documents; It can be an abbreviated typed signature or a simple signature graphic, which is widely recognized as being legally binding and effective in signing electronic documents. A digital signature is another method that is more secure than an electronic signature. It uses encryption and public key infrastructure (PKI) to ensure the authenticity and integrity of electronic documents. The digital signature is created using a mathematical algorithm that generates a unique key associated with the contents of the document and the identity of the signer, verifying the encryption with the signer’s private key. So it can be concluded that Both electronic signatures and digital signatures are used to sign electronic documents. It is widely popular, however. Electronic signatures are convenient and acceptable to some extent, but they are limited in their security. Digital signatures offer a high level of security and are ideal for high-value transactions or sensitive data. To choose to use an electronic signature or a digital signature. depending on the type of document The level of security and legality of the signature.